Membangun Budaya Integritas dalam Generasi Muda melalui Pembelajaran Pendidikan Pancasila - Furnamasari, Yayang Furi; Shafira, Diva; Yulianti, Delis; Kulsum, Maulidah Ummu; Syifa, Nazwa Al; Khoerunisa, Siti; Rizkia, Yusril Fitra; Nurfadillah, Yoane Siti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to explore the role of Pancasila Education learning in building a culture of integrity among Indonesia's young generation. Using exposition and analysis methods, the author explains the concept of integrity culture, the challenges faced, and the role of the younger generation in maintaining and developing the culture. This article uses a qualitative approach through the literature review method. The main source of this research data is articles published online through Google Scholar. Data search is carried out using keywords that are relevant to the focus of the study. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing The results indicate that Pancasila Education learning plays a crucial role in shaping the nationalism, patriotism, and morality character among the young generation, by reinforcing awareness of rights and responsibilities as citizens and cultivating attitudes of empathy, integrity, and accountability. However, the challenges faced include the influence of foreign cultures and the currents of globalization which may shift the identity and values of local culture. Therefore, the integration of Pancasila values into the educational curriculum, supported by innovative teaching methods, as well as the consistent role of teachers and educational institutions, becomes key in building a culture of integrity among the young generation